Microneurosurgery [ aneurysms, arteriovenous malformations - Yasargil, Mahmut Gazi (Thieme classics, 2008)
"Named "Man of the Century" by Neurosurgery, the official journal of the Congress of Neurological Surgeons, Dr. Yasargil has been a pioneer in microneurosurgery for decades. The DVD presents the original video series with hours of comprehensive coverage of microneurosurgical techniques. Each video distills Dr. Yasargil's clinical expertise, guiding the clinician step-by-step through the surgical management of aneurysms and arteriovenous malformations."--Publisher Web site.